Efektivitas Pembelajaran PKn di Sekolah Dasar pada Masa Pandemi Covid-19 - Arfi Purnama Nur Indah; Dinie Anggraeni Dewi; Yayang Furi Furnamasari (Universitas Muhammadiyah Enrekang, 2022)
This covid-19 pandemic has spread to various countries including Indonesia which has a very large influence, not only on the economic, transportation and tourism sectors, but in the education sector as well. Distance learning is considered an educational innovation as well as a solution to answer the challenges of learning in the future. In a pandemic, this research aims at the effectiveness of Civics learning in elementary schools during the Covid-19 pandemic. Effectiveness is a key element to achieve the goals or targets that have been determined in every organization, activity or program. Citizenship Education (citizenship) is a subject that focuses on the formation of citizens who understand and are able to carry out their rights and obligations to become intelligent, skilled, and characterized Indonesian citizens mandated by Pancasila and the 1945 Constitution of the Republic of Indonesia. Young people and students are the next generation of the nation, so in addition to studying the basic material of civic education, we as the next generation of the nation should study the history of the struggle of the Indonesian nation.